Study on Fire Smoke Control in Super-high Building Atrium. (2018) - Xu, Xiao-yuan; Wang, Zhen-hua; Liu, Xuan-ya; Ji, Chao; Yu, Nian-hao; Zhu, Hong-ya; Li, Jing-jing; Wang, Peng-fei
Abstract: In this paper, hot smoke test was carried out in the atrium of 60m high in Shanghai Tower, the law of fire smoke movement and smoke control effect has been studied under different fire release rate and different ventilation conditions. In this paper, the Influence of different air supply volume on mechanical smoke exhaust in the atrium of Shanghai Tower has also been studied by numerical simulation. The results showed that: in the tall atrium, smoke rise rapidly with the speed of 2-3 m/s because of "chimney effect"; Because of the "thermal barrier effect", when the fire power is small, the smoke tends to subside and cannot be effectively discharged; When air supply volume is 50% of smoke exhaust, it is beneficial to exhaust smoke.